Brahmawidyā Dalam Tattwa Sanghyang Mahājñāna - Ida Made Windya (Kamaya: Jurnal Ilmu Agama, 2021)
The ancestors of Hindus in Bali had inherited Brahmawidyā texts through the manuscript of Tattva which has been familiar in the religious live. Meanwhile, the publication regarding Brahmawidyā is really limited in the area of research. Due to that reason, the research regarding Brahmawidyā in the Sanghyang Mahājñana Tattva can be an interesting topic to be analysed. This research aims to analyse Brahmawidyā in the Sanghyang Mahājñana Tattva from the aspect of Panca Sradha as the foundation of faith, and also to obtain a deeper insight on the Divinity aspect in Sanghyang Mahājñana Tattva. The method of this research is a literature study with the approach of qualitative research. This study shows that the comprehension of Brahmawidyā teachings is compulsory for Hindu. It is impossible for Sradha (faith) to be strongly persistent without adequate foundation of Brahmawidyā. This research also shows that the Divinity aspect in the Sanghyang Mahājñana Tattva is monotheism immanent.